2016
DOI: 10.1136/annrheumdis-2016-209954
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetes mellitus associated with disease-modifying antirheumatic drugs and statins in rheumatoid arthritis

Abstract: In RA, incidence of DM is increased. Hydroxychloroquine and abatacept were associated with decreased risk of DM, and glucocorticoids and statins with increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
72
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 46 publications
9
72
2
5
Order By: Relevance
“…This therapeutic advantage of HCQ was also demonstrated in our study2 (see table 1) as shown by Pareek et al 9 for statins, despite the differences in patient characteristics, statin and HCQ doses and durations. This is an important point since both statins and GCs play essential roles in RA and cardiovascular risk management and cannot be avoided because of DM risk.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This therapeutic advantage of HCQ was also demonstrated in our study2 (see table 1) as shown by Pareek et al 9 for statins, despite the differences in patient characteristics, statin and HCQ doses and durations. This is an important point since both statins and GCs play essential roles in RA and cardiovascular risk management and cannot be avoided because of DM risk.…”
supporting
confidence: 88%
“…We appreciate the interest shown by Pareek and Chankurdar1 concerning our recent study on diabetes mellitus (DM) risk associated with disease-modifying antirheumatic drugs and statins in patients with rheumatoid arthritis (RA) 2. They pointed out that statin-associated DM risk in patients with RA might be a more important concern than the risk attributed to glucocorticoids (GCs) due to longer treatment durations 1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, incidence of new-onset diabetes was least with HCQ. In another recent study published in this journal,3 data of 13 669 patients with RA from a longitudinal observational cohort were assessed. The adjusted HRs (95% CI) for diabetes mellitus (DM) were 0.67 (0.57 to 0.80) for HCQ, 1.31 (1.15 to 1.49) for glucocorticoids and 1.56 (1.36 to 1.78) for statins.…”
mentioning
confidence: 99%
“…In the recent article from Ozen et al 1, the authors found increased risk of diabetes mellitus (DM) in patients with rheumatoid arthritis (RA) compared with normal US adult population.…”
mentioning
confidence: 99%